Electrophoretic deposition of antibiotic loaded PHBV microsphere-alginate composite coating with controlled delivery potential - Chen, Qiang; Li, Wei; Goudouri, Ourania Menti; Ding, Yaping; Cabanas Polo, Sandra; Boccaccini, Aldo R. (Colloids and Surfaces B: Biointerfaces, 2015)
Electrophoretic deposition (EPD) technique has been developed for the fabrication of antibiotic-loaded PHBV microsphere (MS)-alginate antibacterial coatings. The composite coatings deposited from suspensions with different MS concentrations were produced in order to demonstrate the versatility of the proposed method for achieving functional coatings with tailored drug loading and release profiles. Linearly increased deposit mass with increasing MS concentrations was obtained, and MS were found to be homogeneously stabilized in the alginate matrix. Chemical composition, surface roughness and wettability of the deposited coatings were measured by Fourier transform infrared (FTIR) spectroscopy, laser profilometer and water contact angle instruments, respectively. The co-deposition mechanism was described by two separate processes according to the results of relevant measurements: (i) the deposition of alginate-adsorbed MS and (ii) the non-adsorbed alginate. Qualitative antibacterial tests indicated that MS containing coatings exhibit excellent inhibition effects against E. coli (gram-negative bacteria) after 1. h of incubation. The proposed coating system combined with the simplicity of the EPD technique can be considered a promising surface modification approach for the controlled in situ delivery of drug or other biomolecules.
Keywords: Alginate; Antibacterial coatings; Drug delivery; Electrophoretic deposition; Microspheres